Expression of retinoid receptors during rabbit lung development - K. Coste; D. Gallot; G. Marceau; J. Jani; J. Deprest; A. Labbé; D. Lémery; V. Sapin (Animal, 2007)
Rabbit lung is often used to study the pathophysiology of some congenital anomalies affecting the lung because its development is very comparable with that of human. Retinoids and the molecular transducers of the retinoic signal play a crucial role in mammalian lung development. In the rabbit, the molecular retinoic pathway has so far been poorly studied. As a first step in elucidating this process, we aimed to identify the retinoic acid receptors (RARs) and retinoid X receptors (RXRs). We cloned a part of the nuclear receptors (RARs and RXRs), and we used reverse transcription - polymerase chain reaction (RT-PCR) and immunohistochemistry assays to demonstrate the presence of RAR (α,β) and RXR (α, β) at all stages of rabbit lung development. Our results initiate further analysis into the molecular and genetic functions of retinoids during normal and pathological rabbit lung development including the surgical model of congenital diaphragmatic hernia.